The a-value of polymineral fine grain samples measured with the post-IR IRSL protocol - Kreutzer, Sebastian; Schmidt, Christoph; DeWitt, Regina; Fuchs, Markus (Radiation measurements, 2014)
Recent post-IR IRSL (pIRIR) dating studies using polymineral fine grains assumed that the a-values obtained for the IRSL signal at 50 °C and the pIRIR signal at higher temperatures (e.g. 225 °C) are identical. However, the a-value of a sample depends on the stimulation method, and the assumption mentioned above remains to be tested. Using five polymineral fine grain samples, this study investigates whether a common a-value can be used for both the IR and the pIRIR signals. Applying the pIRIR protocol, the a-values were measured with three different methods of signal resetting (optical bleaching, end of SAR cycle, heating). In addition, uncorrected α- and β-irradiation induced growth curves were determined for three samples and fitted with single saturating exponential functions. For the investigated samples we found significant mean differences, 0.023 ± 0.012 and higher, in the a-values determined for the IR50 and pIRIR225 signals. Synthetic a-values deduced from uncorrected multiple-aliquot dose response curves seem to confirm this observation. Although, in summary, our results indicate that the practice of using a common a-value should be carefully re-considered, the physical reasons remain to be determined.
Online veröffentlicht: 30. Juni 2014
Gesehen am 01.04.2025